Polyphony in Mary Borden’s selected poems - Fadi Butrus K. Habash (Studies in English Language and Education)
This study examines the manifestation of polyphony in the war poetry of Mary Borden, an American-British poet whose works capture the multiplicity of voices, both heard and silenced, during wartime. It contributes to modernist and postmodernist literary discourse by addressing the overlooked polyphonic dimensions of her poetry. The research focuses on three poems from her collection The Forbidden Zone (1929): At the Somme: The Song of Mud, The Hill, and Unidentified. The data collection and analysis involve close textual examination and application of postmodernist conceptions of polyphony by exploring various forms of polyphony, including dialogical relationships, levels of communication, diversity of voices, styles of discourse, and perspectives to explore how polyphony shapes the structure, unity, and meaning of Borden’s poetry. The findings reveal that Borden manifested polyphony as fragmentation, religious and mythological norms, muted voice, philosophical and religious voices, juxtaposition, vocalized icons, psychological and introspective polyphonic dialogs, and rhetorical voices. They are used to depict the horrors of war, capturing the suffering, anguish, and trauma experienced by soldiers through the fragmented and subjective perspectives of a nurse and an eyewitness. Her use of trench poetry accentuates the emotional turmoil of war, reflecting grief, despair, and anger through a polyphonic and fragmentary style. The research argues that the relationship of multiple voices within these poems reflects the brokenness of nations and the fragmented consciousness of war survivors. By engaging with polyphonic voicing, this analysis demonstrates how Borden’s poetry challenges readers to confront the incompleteness, indeterminacy, and enduring psychological impact of war.